(untitled) (Communications in Mathematical Research, 2021)
In this paper, the λ-central BMO estimates for higher order commutators of Hardy operators on central Morrey space L^q,λ(R^n) are established. In the meanwhile, the corresponding corollary for central BMO estimates is also obtained.